Effects of doping concentration on the surface plasmonic resonances and optical nonlinearities in AGZO nano-triangle arrays - Long, Hua; Bao, Lijiao; Habeeb, Ammar Ayesh; Lu, Peixiang (Optical and quantum electronics, 2017)
Al and Ga co-doped ZnO (AGZO) nano-triangle arrays have been fabricated by nanosphere lithography and pulsed laser deposition methods. By changing the doping concentrations, the surface plasmonic resonance (SPR) peaks of the nano-triangle arrays were tuned in the infrared range from 2.4 to 3.6 μ m. The SPR peaks show blue shift with Al dopant increasing. The nonlinear optical properties of the AGZO nano-triangle arrays were investigated by Z-scan method with femtosecond laser. The results show that the nonlinear optical properties of the nano-triangle arrays could be tuned by adjusting Al doping concentration. And the AGZO nano-triangle arrays show nonlinear optical properties suitable for applications on all-optical switching.